An Introduction to Database Systems - C.J. Date (Addison-Wesley, 2000)
This book provides a solid grounding in the foundations of database technology and gives some ideas of how the field is likely to develop in the future. Emphasizing insight and understanding rather than formalisms, Chris Date has divided the book into six parts: Basic Concepts, The Relational Model, Database Design, Transaction Management, Further Topics, and Object and Object/Relational Databases. This comprehensive introduction to databases reflects the latest developments and advances in the field of database systems. Throughout the book, there are numerous worked examples and exercises for the reader--with answers--as well as an extensive set of annotated references